2016
DOI: 10.1002/pat.3792
|View full text |Cite
|
Sign up to set email alerts
|

Modification of acrylic bone cements by poly(ethylene glycol) with different molecular weight

Abstract: The high polymerization temperature of acrylic bone cements can cause arthroplasty failure because of the thermal necrosis of surrounding bone tissue. To reduce this undesired effect we have developed novel acrylic bone cement composites containing a phase change material (PCM). As PCM poly(ethylene glycol) (PEG) of different molecular weight was applied and the effect of its incorporation on curing parameters, mechanical and morphological properties of acrylic bone cement was investigated. A significant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…After active ingredients were removed with methanol, the MCs became softer, and the MCs were more likely to become dented and collapse, thereby affecting the release performance of the MCs. This result is similar to the conclusion proposed by Król and Pielichowska, who showed that the use of PEG modifications of different molecular weights can considerably decrease the mechanical strength of bone cement 28 . As shown in A3, B3, C3 and D3, the MCs prepared with PEG200, PEG400, PEG800 and PEG1500 had similar particle sizes of approximately 5 μm.…”
Section: Resultssupporting
confidence: 90%
“…After active ingredients were removed with methanol, the MCs became softer, and the MCs were more likely to become dented and collapse, thereby affecting the release performance of the MCs. This result is similar to the conclusion proposed by Król and Pielichowska, who showed that the use of PEG modifications of different molecular weights can considerably decrease the mechanical strength of bone cement 28 . As shown in A3, B3, C3 and D3, the MCs prepared with PEG200, PEG400, PEG800 and PEG1500 had similar particle sizes of approximately 5 μm.…”
Section: Resultssupporting
confidence: 90%
“…Finally, some developments have sought to reduce the polymerization temperature of the bone cement mixture. For example, by including poly(ethylene glycol) (PEG) to the blend, the heat of polymerization is absorbed by the PEG, reducing the overall temperature of the treatment (Król & Pielichowska, 2016). (Leggat, Smith, & Kedjarune, 2007;Pascual et al, 1999).…”
Section: Improvements For Bone Cementmentioning
confidence: 99%
“…[1][2][3] The use of nonbiodegradable materials may cause deterioration of surrounding bone tissue leading to repeated surgeries and long inflammatory response due to fragmentation and particulate formation. Several research efforts have been focused on the development of biodegradable polymers and bone cements [4][5][6][7][8] ; however, most of these medical devices are made of biodegradable polyesters and polyanhydrides, which are semicrystalline thermoplastics. These polymers have limited applications in such areas as in situ orthopedic bone filling and fixation and soft tissue repairs because they cannot be processed into the desired shapes and forms during surgery.…”
Section: Introductionmentioning
confidence: 99%